The antikythera mechanism: The prove of the accuracy of the astronomical calculations based on it - Efstathiou, Kyriakos; Efstathiou, Marianna; Basiakoulis, Alexandros; Kokkinos, Neofytos (My University, 2021)
The Antikythera Mechanism is the oldest extant complex geared device, an amazing analogue computer. It was built approximately 2150 years ago. The device was operated manually by a user, setting a date in a dial. All necessary calculations were made using a set of gears (at least 39), while the results were displayed on several scientific scales. The Mechanism was used to calculate astronomical phenomena, such as solar and lunar eclipses. After an extensive description of the Mechanism, the main objective of the following paragraphs is to demonstrate the accuracy of its predictions.
Keywords: Ancient Astronomy; Ancient Technology; Antikythera Mechanism; Egyptian Calendar; Gears